The Legality of Foreign Military Activities in the Exclusive Economic Zone under UNCLOS - Jing Geng (Merkourios, 2012)
During negotiations for the United Nations Convention on the Law of the Sea (UNCLOS), military activities in another state's Exclusive Economic Zone (EEZ) were a point of contention. Currently, the issue remains controversial in state practice. UNCLOS attempts to balance the differing interests of coastal and maritime states, but is silent or ambiguous on the legality of military operations in foreign EEZs. Coastal states seek to assert increasing control over their maritime zones while maritime states prioritize the freedom of navigation. This article examines the competing views on these issues in the context of the 2009 Impeccable incident between China and the United States that occurred in the South China Sea. The issue of military activities in the EEZ will continue to be a complex subject, without clear definitions in the nature and scope of permissible activity. As state practice evolves, the potential for hostilities is high, particularly in semi-enclosed sea areas such as the South China Sea. This article concludes that states should create dialogues and form agreements to help clarify the contours of military activity in the EEZ, focusing on mutual interests, interdependence, and coexistence rather than perceiving the ocean as a zero-sum resource.